Influência da forma do assoreamento na vazão regularizada de reservatórios do Estado do Ceará - Campos, Jody (2015)
This paper presents an evaluation of the influence of different forms of deposition silted mass of Ceará reservoirs, and their impact on the regulated flow. We investigated three different forms of silting, called this work of alpha 1 1), alpha 2 () and alpha 3 (3). After defining these forms, curves were constructed Cota x Area x Volume (VACs) reservoirs. Using the Simres program for hydrological reservoir simulation was possible to compare project information with the current situation of the reservoirs, and assess how much they lost in supply of regulated flow. Furthermore, it presents an evaluation of silting and its impact on future conditions (50 to 100 years) in order to promote a more accurate planning in the management of water resources. Was selected five strategic reservoirs of Ceará State Óros, Banabuiú, Cedar, Cooker and White Stones, of whom there Shells of more than a hundred years completed. Was obtained for alpha 1 and alpha 2 models similar results, showing little difference between these two models, but for the alpha 3 model the results are quite different from the other two and with significant impact in terms of loss of regulated flow. The results show the importance of monitoring the tanks and see how they are silting